2000
DOI: 10.1073/pnas.240462897
|View full text |Cite
|
Sign up to set email alerts
|

Gene correction in hematopoietic progenitor cells by homologous recombination

Abstract: Homologous recombination (gene targeting) has many desirable features for gene therapy, because it can precisely correct mutant genes and restore their normal expression, and random nonhomologous integration of DNA is infrequent in cells in which homologous recombination has occurred. There are, however, no reports of attempts to use homologous recombination to correct mutant genes in normal hematopoietic stem cells (HSCs), which are prime cells for therapy of a variety of hematological and other conditions, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The observation reported here, however, suggests that it may be possible to position a selectable marker cassette near the human ␤-globin gene in a manner that does not disrupt its expression; direct experiments to test this hypothesis using ES cells containing a copy of the human ␤-globin gene cluster should now be performed. The recent observation by Hatada et al 42 that hematopoietic progenitor cells have the machinery required to perform homologous recombination further supports this approach. However, significant obstacles remain.…”
Section: Discussionmentioning
confidence: 82%
“…The observation reported here, however, suggests that it may be possible to position a selectable marker cassette near the human ␤-globin gene in a manner that does not disrupt its expression; direct experiments to test this hypothesis using ES cells containing a copy of the human ␤-globin gene cluster should now be performed. The recent observation by Hatada et al 42 that hematopoietic progenitor cells have the machinery required to perform homologous recombination further supports this approach. However, significant obstacles remain.…”
Section: Discussionmentioning
confidence: 82%
“…However, although site-specific homologous recombination has been achieved by using hematopoietic progenitor cells in one study (23), it has not been possible to achieve this goal using tissue-specific stem cells. The present study demonstrates that it is possible to apply the concept and techniques of ES cell manipulation to spermatogonial stem cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…There has been uncertainty that homologous recombination can occur at a usable frequency in tissue-specific stem cells (23). Several studies have indicated a low mutation frequency in spermatogonial stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hatada et al [17] used gene targeting to correct a defective hypoxanthine phosphoribosyltransferase (HPRT) gene in hematopoietic progenitor cells. The approach was similar to gene targeting with ES cells or NT, in that selection was used to enrich for targeted outcomes.…”
Section: Models Of Hrmentioning
confidence: 99%